Comparison of Vegetation Vitality Data and Soil Moisture Measurements at the Prosper-Haniel Closed Mine Site - Pawlik, Marcin; Bernsdorf, Bodo; Rudolph, Tobias; Than Thar Lwin, Nyein; Jaeckel, Julian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Effective management of flood-prone areas, particularly polders, is critical for ecological balance and human safety. This study focuses on mining-induced polders in the Ruhr region, emphasizing the need for sustainable flood protection strategies amidst changing climatic conditions. By analyzing data from the Copernicus Sentinel 2 satellite mission and ground-based measurements, the study investigates vegetation response to variable soil moisture.
Keywords: polder areas; vegetation condition; NDVI; soil moisture; soil temperature